Habitat mapping of remote coasts: Evaluating the usefulness of lightweight unmanned aerial vehicles for conservation and monitoring. (November 2019) - Castellanos-Galindo, Gustavo A.; Casella, Elisa; Mejía-Rentería, Juan Carlos; Rovere, Alessio
Abstract: Unmanned aerial vehicles (UAVs) have the potential to be an important tool providing low-cost but sufficiently precise mapping products to support environmental management. In this study, we present possible applications of UAVs to map and monitor three representative coastal tropical habitats: mangroves, rocky shores and coral reefs. We conducted UAVs surveys in a Marine Protected Area (MPA) of the tropical eastern Pacific region to investigate the suitability and usefulness of using this tool in a remote area for a variety of management and monitoring purposes. For mangrove ecosystems, we evaluated the potential of UAV-derived data to estimate canopy cover. On an intertidal rocky shore, we evaluated the potential of UAVs to obtain a detailed relative topographic position index that can be used to correlate the distribution patterns of resident and transient fauna. Finally, we compared the standard diver-based coral reef mapping approach used at the MPA with the use of a map produced with the UAV. Our results suggest that the use of UAVs by conservation practitioners in MPAs with diverse habitats, such as in the tropics, is likely to improve the knowledge of the MPAs environments and provide highly detailed information for monitoring helping to understand the nursery function of these inter-connected tropical habitats, at a reduced cost. This tool, therefore, has the potential to support conservation measures in a more effective way.